Bidan Lewu as Local Determinant Factors in Pregnancy and Childbirth Care (Study in the Dayak Ngaju Tribe in Kotawaringin Timur District) - Sigit Nurfianto1,2, Usman Hadi3 , Windhu Purnomo4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: he coverage of antenatal care was low in Kotawaringin Timur in 2019. The first visit duringpregnancy (K1) was 81.20%, and the fourth visit during pregnancy (K4) was 74.50%, with a national visitstandard of 95%. Kotawaringin Timur’s adolescent pregnancy rates reached 66.89%, higher than the otherdistricts’ average rate in Central Kalimantan Province. The adolescent pregnant women had a low intentionof antenatal care as much as 84.48% in 2019.Objective: This study aimed to analyze the local determinant factors that contribute to adolescent pregnantwomen’s intention in carrying out antenatal care.Methods: This study was qualitative research. The data were collected by a focus group discussion (FGD)method and in-depth interviews in four sub-districts of Kotawaringin Timur. The informant of this studywas 45 people consisting of 44 adolescent pregnant women and one traditional leader (Damang). Data wereprocessed using the self-view value domain method.Result: Adolescent pregnant women’s intentions during antenatal care were influenced by their responsesto the availability and ability of people who help or assist the process of pregnancy and childbirth care.Adolescent pregnant women prefer traditional birth attendants or bidan lewu as their pregnancy nursesand childbirth assistants. It was triggered by the trust of adolescent pregnant women towards bidan lewubecause they were more experienced, attentive, and patient in serving. The involvement of bidan lewuduring pregnancy and childbirth has been used for generations.Conclusion: Some of the Local determinant factors related to pregnancy and childbirth care are the presenceof bidan lewu who have been used for generations to treat pregnancy and assist in the childbirth process.